1980
DOI: 10.1113/jphysiol.1980.sp013516
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of arterial pressure and heart rate in fetal, new‐born and adult sheep.

Abstract: SUMMARY1. Baroreflex activity was assessed in nine fetal, four new-born and six adult sheep, using the relationship between heart period and arterial pressure. Arterial pressure was raised either by inflating a balloon in the dorsal aorta, by rapid intravenous injection of phenylephrine or methoxamine, or by slow intravenous infusion of methoxamine.2. In the fetus the three methods gave different estimates of baroreflex sensitivity (balloon, 1-3 + 0 7 mmHg; injections, 5-4 + 0.5 msec mmHg; infusions, 7-2 + 0 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 14 publications
4
47
0
1
Order By: Relevance
“…This reflex is active but functionally immature at 36 wk and still relatively weak at 40 wk (27). If the threshold for baroreflex activation is slow to reset to the usual postnatal range, dynamic variations in pressure may be wider than expected and remain so for much longer than is normal after birth, as we observed (28).…”
Section: Discussionsupporting
confidence: 53%
“…This reflex is active but functionally immature at 36 wk and still relatively weak at 40 wk (27). If the threshold for baroreflex activation is slow to reset to the usual postnatal range, dynamic variations in pressure may be wider than expected and remain so for much longer than is normal after birth, as we observed (28).…”
Section: Discussionsupporting
confidence: 53%
“…Although there have been other investigations into the efferent limb of the arterial baroreflex control of heart rate during postnatal maturation in rabbits, swine and sheep (Bloor, 1964;Dawes et al 1980;Tomomatsu & Nishi, 1982;Palmisano et al 1989;Segar et al 1992;Patton & Hanna, 1994), many of these have been conducted on anaesthetised or sedated, paralysed and artificially ventilated animals, or have evaluated only a portion of the heart rate-blood pressure relationship, making the results difficult to interpret. Taken together, there is no generalised agreement as to whether the gain of the arterial baroreflex decreases remains constant or increases with postnatal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, it is shown that the BR is impaired in the fetus and the newborn and develops further during postnatal life (7)(8)(9). The impairment in BR function is due to maturational changes in the autonomic pathways (10).…”
mentioning
confidence: 99%